Wordplay: The Aesthetics in Srisawat Pichitworakarn’s Songs - Phakkhaphanon, Sunan (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
Srisawat Pichitworakarn’s songs are aesthetically outstanding and unique due to his beautifully written lyrics and melodies. Fifty of his love songs were analyzed in terms of the mechanics employed and the song meanings conveyed to the audience. The findings are as follows: The use of reduplicative words and phrases can be categorized into 2 types: the use of the Diacritic Mai-Yamok (a mark for the repetition of a word or the string of words preceding it); the use of reduplicative words and phrases in either the same or a different sentence. The use of synonymous compounds can be categorized into 2 types: 2 synonymous compounds adjacent to each other; 2 synonymous compounds separate from each other. The use of reduplicative words and phrases together with synonymous compounds can be categorized into 3 types: synonymous compounds preceded by reduplicatives, reduplicatives preceded by synonymous compounds, and synonymous compounds preceded by reduplicative phrases. With his elaborate word choice and perfect mechanics used in composing the songs, Srisawat Pichitworakarn is no doubt recognized as one of Thailand’s greatest composers. His songs are profoundly touching in both melody and lyrics to Thai music lovers.